Thermal Conductivity of Mixed Aqueous Solutions of NaCl, СаСl2 and KCl Salts close by Saturation Line - V. S. Eldarov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The paper contains experimental data on thermal conductivity of mixed aqueous solutions of salts within the temperature range from 20 to 300 °C and with various electrolyte concentrations in mass percentage. Thermal conductivity of H20-NaCl-CaCl2-KCl system at high temperatures has been studied for the first time. The experimental results of the present investigations have been generalized within the relative coordinates, namely: λ/λ0 and T/T0, (Т0 = 293,15 К; λ0 - thermal conductivity of a solution at T0 temperature). An empirical equation of thermal conductivity in the parabolic form has been obtained.